Adhesive composition and method for producing wood material and wood material
By using a combination of polymer binder, phase transfer catalyst and silane compounds in the production of wood materials, the problem of adhesive hardening speed control and diffusion is solved, and a safe, fast and low-cost manufacturing process is achieved, and a safe, fast and low-cost manufacturing process is improved. Product quality.
Patent Information
- Application Number
- CN202380044863.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-05-30
- Publication Date
- 2025-01-14
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition for producing wood materials, in particular board-like wood materials, such as wood particle boards or wood fiber boards, in particular OSB, HDF or MDF boards, as well as plywood and glued laminates, a method for producing such an adhesive composition, a method for producing such a wood material and such a wood material. Background Art
[0002] Various adhesive compositions, in particular glues, are used for the production of wood materials. Depending on the application, different adhesive compositions are preferred or particularly suitable. Adhesive compositions based on urea / formaldehyde have proven to be particularly suitable for wood panels that are subsequently used in furniture production or interior design.
[0003] For applications where increased air humidity or subsequent moisture from adjacent components is expected, such as floor coverings, urea-formaldehyde glues are often used, optionally reinforced with melamine, with the amount of adhesive composition being increased to take into account the increased requirements.
[0004] For wood-based panels used in areas with high humidity or in direct contact with water, urea-formaldehyde adhesives reinforced with melamine resins, phenolic resins or polymeric diphenylmethane diisocyanate (PMDI) have proven to be suitable. Plywood, particleboard and OSB (oriented strand board) are particularly suitable for various applications here. Although all adhesives that are not hydrolyzed by moisture or water can generally be used for the above-mentioned wood materials, polymeric diphenylmethane diisocyanate (PMDI) has proven to be particularly suitable for OSB.
[0005] When producing wood-based materials, the basic goal is often not only to use the facilities as efficiently as possible, but also to use the raw materials as efficiently as possible. These two goals often conflict with each other. For example, in order to achieve the highest possible system speed, an increased amount of adhesive must be used. However, if the operating method is optimized with respect to the amount of adhesive, the speed of the system needs to be sacrificed. In general, the limiting factor is the heat transfer from the press heating plate to the middle of the wood chip or fiber cake. Depending on the method of proceeding, this conflict of goals can lead to higher fixed costs for the facilities used or higher material costs. This problem can be reduced to a certain extent by using hardeners or aggregates that accelerate the introduction of heat into the wood chip or fiber cake.
[0006] However, it must be taken into account that hardeners and the like, while accelerating the curing speed, can lead to pre-curing of the adhesive during plant downtime. This is particularly problematic when using polymeric diphenylmethane diisocyanates. Such polymer adhesives react with many catalysts at room temperature and thus lead to pre-curing. It is therefore advantageous to use catalysts that make the curing easier to control and that cause as little pre-curing as possible.
[0007] Use suitable catalyst, adhesive composition only solidifies in a targeted manner at the desired time point, however, this leads to the following disadvantages: in the process of the method, the time that uncured adhesive contacts with the wood material to be bonded is longer, and therefore penetrates more into it. Here, studies show that, particularly when using wood materials such as PMDI to bond, especially when the wood chips of oriented strand board (OSB) made of softwood, adhesive is particularly easy to fall off or diffuse into the wood. One of the reasons is that hydrophobic PMDI adhesive is particularly easily absorbed by the wood surface, and the wood surface contains more or less fatty acid according to the season. This means that adhesive can only be partially used for bonding the wood chips in this area, and therefore requires a large amount of adhesives to achieve sufficient bonding. This leads to an increase in production costs, and sometimes also leads to the undesirable application of adhesive. In addition, because adhesive penetrates into the wood material, there are technical limitations in the facilities used and possible method management. Summary of the invention
[0008] The object of the present invention is therefore to provide an adhesive composition for producing wood materials, in particular board-shaped wood materials, a method for producing such wood materials and a wood material in which the curing speed of the adhesive can be controlled in a targeted manner while preventing the adhesive from spreading in the wood materials to be bonded as much as possible, thereby achieving a safe, fast and cost-effective manufacturing process with a minimized amount of adhesive and without reducing product quality.
[0009] According to the invention, this object is achieved by an adhesive composition for producing a wood material according to claim 1, a method for producing a wood material according to claim 10 and a wood material according to claim 15. Advantageous developments of the invention are specified in the dependent claims.
[0010] The adhesive composition according to the invention for producing wood materials, in particular board-like wood materials, such as wood particle boards or wood fiber boards, in particular OSB, HDF or MDF boards, as well as plywood and glued laminates comprises an organic phase containing at least one polymer adhesive, an aqueous phase, at least one phase transfer catalyst for accelerating the curing of the polymer adhesive, and a hydrophilic agent comprising at least one silane compound or formed from at least one silane compound for increasing the hydrophilicity of the polymer adhesive and / or reducing the penetration of the polymer adhesive into the material to be bonded of the wood material, in particular the wood chip material to be bonded.
[0011] The present invention further relates to a method for preparing an adhesive composition according to the present invention, the method at least having the steps of providing at least one silane compound, preferably at least two different silane compounds, particularly silane compounds of general chemical formula (I) and / or (II), and adding at least one polyol compound to the at least one silane compound, and preferably adding at least one catalyst, particularly acid to a mixture of at least one silane compound and at least one polyol compound. Subsequently, the reaction mixture is precipitated and / or separated from at least one silane compound and at least one polyol compound, and a phase transfer catalyst is added. Simultaneously or preferably, at least one polymer binder system is then finally added to the phase transfer catalyst and / or to the reaction mixture separated from at least one silane compound and at least one polyol compound. In addition, the adhesive composition according to the present invention can also be produced using only silane compounds without the need for polyols as reactants, thereby not requiring corresponding catalysts. In this case, only at least one silane compound as a hydrophilic agent, a phase transfer catalyst and at least one polymer binder are mixed with each other.
[0012] Furthermore, the present invention relates to a method for producing a wood material, in particular a board-shaped wood material, such as a wood particle board or a wood fiber board, in particular an OSB, HDF or MDF board, as well as a plywood and a glued laminate, wherein firstly a wood chip material is produced and / or provided, to which a binder composition is subsequently added, wherein the binder composition has an organic phase containing at least one polymer binder and a second aqueous phase immiscible with the organic phase, a phase transfer catalyst for accelerating the curing of the polymer binder, and a hydrophilizing agent comprising at least one silane compound to increase the hydrophilicity of the polymer binder and / or to reduce the penetration of the polymer binder into the wood material, and then finally a wood material is formed from the bonded wood chip material, in particular by pressing into a board-shaped wood material.
[0013] The wood material according to the present invention, in particular the wood material produced by the method according to the present invention, has a wood chip material and at least one cured adhesive composition in at least one layer of the wood material, in particular the adhesive composition according to the present invention, wherein the adhesive composition has at least one cured polymer adhesive, a phase transfer catalyst for accelerating the curing of the polymer adhesive, and a hydrophilizing agent comprising at least one silane compound to increase the hydrophilicity of the polymer adhesive and / or reduce the penetration of the polymer adhesive into the wood chip material to be bonded of the wood material.
[0014] Finally, the present invention relates to the use of the adhesive composition according to the invention with a phase transfer catalyst for the production of wood materials, and preferably for the production of wood particleboards or wood fiberboards, in particular OSB, HDF or MDF boards, and also plywood and glued laminates.
[0015] The inventors have recognized that the use of phase transfer catalysts in combination with hydrophilic compounds in adhesive compositions for wood materials allows for targeted control of reactivity and curing speed, while successfully minimizing or even substantially preventing migration of the adhesive or penetration of the wood to a large extent, so that at the same time small amounts of adhesive can be used and a particularly uniform and targeted curing can be achieved.
[0016] Furthermore, the combination of a hydrophilizing agent and a phase transfer catalyst has the advantage that the heat required for setting or hardening acts particularly evenly on the adhesive, since at least a large part of the adhesive is on the surface of the wood chip material and not inside the wood, so that a particularly even catalyst effect can be achieved.
[0017] Adhesive compositions are to be understood as compositions of sawdust materials which are provided for the addition and bonding of wood, and in particular of wooden materials, wherein the adhesive composition is preferably formed in such a way that the wooden material can be produced only from sawdust materials and adhesives. However, in principle, further components, such as auxiliary materials and fillers, can also be added to the wooden material. Here, the adhesive composition can be pre-formulated and / or can be formed from a single component.
[0018] Or, adhesive composition can also be formed by several components, particularly two components that are provided separately, only before use or during use, they are put together and mixed.At this especially, organic phase can be a kind of component and water can be another kind of component, wherein phase transfer catalyst and / or hydrophilic agent are preferably included in water.But, it can also be imagined in addition that hydrophilic agent and / or phase transfer catalyst provide as salt or as dissolved substance, provide separately as the third component and / or the fourth component, or add when using.Phase transfer catalyst and hydrophilic agent also can be prepared in situ.The ready-to-use adhesive composition that is made up of one or more components that have mixed is generally referred to as glue or resin, and adhesive is therefore applied to wood chip material and is referred to as gluing.
[0019] Furthermore, it is particularly conceivable that the various components of the adhesive composition meet only on the surface of the wood to be bonded, in particular wood chip material, wherein preferably only the first component, in particular the aqueous phase and / or the phase transfer catalyst and the hydrophilizing agent, are applied to and / or into the wood chip material, and then an organic phase with at least one polymer binder, in particular an isocyanate binder, is added.
[0020] The wood material can in principle be any material, preferably a material whose major part, at least 90%, consists of wood, plant fibers and / or materials made therefrom, by connecting several pieces of this material with the adhesive composition, except for the adhesive composition. It is preferably at least one wood chip material. The wood material can basically have any shape, wherein board-shaped wood materials are preferred, in particular wood cellulose and / or fiber-containing boards, particle boards and / or coarse particle boards.
[0021] The sawdust material can in principle have any plant debris and / or fibers and is preferably formed essentially from plant debris. The sawdust material is particularly preferably made of wood. The sawdust material is particularly preferably composed of long chips (wood chips) and / or coarse chips, in particular for the production of coarse particleboard, also known as OSB (oriented strand board). The sawdust produced or provided for the production of coarse particleboard can have the following dimensions: a length of 50 to 200 mm, preferably 70 to 180 mm, particularly preferably 90 to 150 mm; a width of between 5 and 50 mm, preferably 10 to 30 mm, particularly preferably 15 to 20 mm; and a thickness of 0.1 to 2 mm, preferably 0.3 to 1.5 mm, particularly preferably 0.4 to 1 mm. For particleboard, the sawdust size of the cover layer and / or the middle layer is preferably in the range of <1 mm to about 30 mm.
[0022] Although the shaping of the wood material can in principle be carried out in any manner, it is preferably carried out as a continuous process, in particular by spreading the glued wood chip material onto a conveyor, in particular a conveyor belt, and / or by pressing to bond the wood chip material into the wood material. The shaping and in particular the pressing of the wood material is preferably carried out at high pressure and / or high temperature, preferably at least 150° C., particularly preferably 170° C. to 220° C., very particularly preferably 180° C. to 220° C.
[0023] Particularly preferably, the glued wood chip material for producing the coarse-particle board is spread in the spreading device alternately longitudinally and transversely in the production direction, so that the wood chip material is arranged transversely, particularly preferably in at least three layers, in particular a lower cover layer, a middle layer and an upper cover layer. The spreading direction of the lower cover layer and the upper cover layer is preferably the same and / or deviates from the spreading direction of the middle layer.
[0024] The chip material is preferably produced by stripping debarked logs, preferably softwood, in the longitudinal direction and / or using a rotating knife. Furthermore, the chip material produced is preferably dried before the addition of the binder, in particular in order to reduce the natural moisture of the chip material at high temperatures. The moisture content of the dried chip material is particularly preferably below 10%, very particularly preferably below 7%, in order to avoid cracking during the subsequent pressing process and / or to avoid strong steam formation during the pressing process.
[0025] Adhesive composition is added to the wood chip material preferably at least part of the wood chip material as the starting material of wood material and preferably all is coated.The adhesive composition is preferably applied on the wood chip material in the form of fine distribution.Perhaps, it is conceivable that at first the first component of the adhesive composition is applied, or the wood chip material is soaked therein, and then the second component is applied.The amount of the adhesive composition, particularly when using PMDI as adhesive, is preferably based on 1 to 10 weight % of the total amount of the wood chip material, particularly preferably 1.5 to 5 weight %, particularly preferably 2 to 5 weight %, and particularly preferably 2 to 3 weight %.
[0026] In the case of the wood material according to the invention, the adhesive composition preferably hardens completely after its production, wherein the isocyanate adhesive particularly preferably has reacted with the water of the aqueous phase to form carbamic acid and / or further to form the corresponding amine and / or polyurea. In this case, the cured adhesive composition preferably consists essentially of polyurea, phase transfer catalyst and / or other components of the organic phase and / or aqueous phase.
[0027] According to the invention, the adhesive composition has at least one polymer adhesive and preferably at least one isocyanate adhesive. In principle, in particular, depending on the desired properties of the produced wood material, the adhesive composition can have only a single polymer adhesive or a mixture of multiple polymer adhesives, wherein all polymer adhesives are particularly preferably polyurethane adhesives and / or each have at least one isocyanate adhesive or are based on at least one diisocyanate. The proportion of all adhesives in this adhesive composition is preferably between 60% and 100%, particularly preferably at least 85%, very particularly preferably at least 95%. In this, polymer adhesives, in particular polymeric diphenylmethane diisocyanate, are preferably used as pure adhesives and / or no further water is added to the organic phase. The proportion of water or the proportion of the aqueous phase in the adhesive composition is preferably 0 to 15%, particularly preferably 0.01 to 10%, very particularly preferably 0.5 to 8%.
[0028] According to the invention, the adhesive composition has at least one, preferably exactly one, phase transfer catalyst, but in principle it is also conceivable to use several chemically different phase transfer catalysts simultaneously. The phase transfer catalyst of the invention is essentially capable of transferring components of the aqueous phase, in particular water itself, into a non-aqueous phase or an organic phase, in particular into a polymeric adhesive and / or an isocyanate adhesive, in which case water is particularly preferably a reactant for curing the adhesive. Therefore, the phase transfer catalyst preferably transfers water from the aqueous phase into the organic phase, where a reaction with the polymeric adhesive, in particular an isocyanate, can occur, and then releases the phase transfer catalyst again.
[0029] Therefore, the phase transfer catalyst accelerates the curing reaction of the adhesive, but it does not directly participate in the reaction itself. Particularly preferably, the phase transfer catalyst is selected so that it does not participate in the isocyanate groups of the activated adhesive. The phase transfer catalyst can reduce the required reaction temperature and / or shorten the reaction time, and also makes the reaction kinetics easy to control. Preferably, there is a linear relationship between the gel time or the duration of hardening and the amount of the phase transfer catalyst.
[0030] Hydrophilic agents are essentially substances or mixtures of substances that influence the hydrophilic properties of adhesives and in particular increase the hydrophilicity. For this purpose, the hydrophilic agent preferably has at least one hydrophilic region and at least one hydrophobic region, wherein the hydrophobic region further preferably interacts directly with the adhesive composition and / or the polymeric binder contained therein.
[0031] Hydrophilic agent can be a pure single substance or a mixture of substances at this, wherein hydrophilic agent can be a mixture of multiple substances produced by reaction in particular. Through the reaction of at least one silane compound and at least one polyol, a compound or reaction mixture is first formed, which shows stronger hydrophilicity on one side of the molecule due to a large number of OH groups in the polyol. On the other hand, due to the specially modified silane, the molecule produced by the silane compound and the polyol has a reactive group, which can react with the OH group of polymer adhesives, such as PMDI glue or wood. These new compounds and the macromolecules formed by condensation with polymer adhesives or glue are no longer able to pass through the hydrophobic fatty acid layer of wood chip material due to hydrophilic residues. Thus, the adhesive composition of the present invention is retained on the surface of wood chip material or fiber and does not diffuse into the wood matrix. Therefore, hydrophilic agent preferably works by providing hydrophilic anchors for polymer adhesives. However, as a substitute for reaction product, silane or silane compound and particularly corresponding modified silane compound can also be used as hydrophilic agent.
[0032] In order to be able to control the reaction of at least one silane compound with at least one polyol, a catalyst is preferably added. Particularly suitable catalysts are inorganic acids and / or organic acids, which are particularly preferably selected from the group comprising phosphoric acid, acetic acid, p-toluenesulfonic acid, hydrochloric acid, formic acid or sulfuric acid. Ammonium salts such as ammonium sulfate that react as weak acids are also suitable. However, p-toluenesulfonic acid is particularly preferred here.
[0033] The use of sodium glycerophosphate has been shown to be particularly suitable for precipitation of reaction mixtures from at least one silane compound and in particular at least one compound of formula (I) and / or (II) and at least one polyol compound. Other precipitants that may be considered are alkalis, such as NaOH, KOH or ammonium hydroxide solutions. The precipitant is preferably added to the reaction mixture together with water. In this way, the reaction product is concentrated in the aqueous phase and separated from the hydrolyzate (such as ethanol).
[0034] Although in principle at least any phase transfer catalyst can be used, in an advantageous embodiment of the adhesive composition, the phase transfer catalyst has onium ions, preferably ammonium, phosphonium and / or sulfonium ions, and particularly preferably triethylbenzylammonium chloride. In addition, at least one phase transfer catalyst can also be a crown ether, in particular 12-crown-4.
[0035] In a preferred embodiment of the adhesive composition according to the invention, the polymeric binder is exclusively a polyurethane binder based on isocyanate binders, preferably based on aromatic polyisocyanates, in particular polydiphenylmethane diisocyanate (PMDI), toluene diisocyanate (TDI) and / or diphenylmethane diisocyanate (MDI). Polymeric diphenylmethane diisocyanates are particularly preferred. Particularly preferably, the only polymeric binder is a polyurethane binder based on polymeric diphenylmethane diisocyanate. In general, the content of polymeric binder in the adhesive composition is preferably at least 70% by weight, particularly preferably at least 80% by weight, most preferably at least 95% by weight.
[0036] In a likewise preferred embodiment of the adhesive composition according to the invention, more than one polymeric binder can also be used. In principle, in particular, a variety of polyaddition binders can be used, for example epoxy resins, polycyanurates and / or polyurethane binders, in particular polyurethane binders based on polydiphenylmethane diisocyanate (PMDI), wherein all polymeric binders are particularly preferably based on at least one diisocyanate-based binder.
[0037] The hydrophilic agent preferably comprises at least one polyol, and in particular, the hydrophilic agent is formed by the reaction of at least one silane compound with at least one polyol. At least one polyol of the hydrophilic agent is preferably selected from the group of higher alcohols comprising tetravalent, pentavalent, hexavalent sugar alcohols or as polyol compounds having more than six hydroxyl groups. It is also conceivable to use normal polyethylene glycol and normal polyvinyl alcohol as polyols. Based on the total amount of the adhesive composition, the amount of the polyol compound in the adhesive composition is preferably 5 to 50% by weight, particularly preferably 10 to 30% by weight, and very particularly preferably 5 to 10% by weight.
[0038] According to the particularly preferred embodiment of the adhesive composition of the present invention, it is also provided that at least one sugar alcohol is selected from the group of threitol, erythritol, pentaerythritol comprising tetrahydric alcohol, arabitol, adonitol, xylitol and sorbitol, mannitol, dulcitol, dipentaerythritol of hexahydric alcohol.Sugar alcohol is also referred to as reducing sugar.It is also possible to use higher alcohols with more than six hydroxyl groups, for example seven or eight hydroxyl groups.Suitable polyglycol is for example polyethylene glycol or polypropylene glycol.However, the use of sorbitol has been shown to be particularly advantageous.
[0039] According to a particularly preferred embodiment of the adhesive composition of the invention, the at least one silane compound is a compound of the general formula (I)
[0040] R a SiX(4-a)(I),
[0041] Or general chemical formula (II)
[0042] O b X c (OH) d R e SiO(4-bcde) / 2(II),
[0043] in
[0044] -X is H, OH or a hydrolyzable residue selected from the group consisting of halogen, alkoxy, carboxyl, amino, mono- or di-alkylamino, aryloxy, acyloxy, alkylcarbonyl,
[0045] -R is a non-hydrolyzable organic residue R selected from substituted and unsubstituted alkyl, substituted and unsubstituted aryl, substituted and unsubstituted alkenyl, substituted and unsubstituted alkynyl, substituted and unsubstituted cycloalkyl, which can be interrupted by -O- or -NH-,
[0046] And among them
[0047] - R can have at least one functional group Q selected from the group comprising epoxy, hydroxyl, ether, amino, monoalkylamino, dialkylamino, substituted and unsubstituted anilino, amide, carboxyl, alkynyl, acrylic, acryloxy, methacrylic, methacryloyloxy, mercapto, cyano, alkoxy, isocyanate, aldehyde, alkylcarbonyl, anhydride and / or phosphoric acid,
[0048] - R and X can be the same or different from each other, and
[0049] -a=0,1,2,3, especially 0 or 1,
[0050] - b, c, d = 0 or 1, and
[0051] -e=1, 2, 3.
[0052] The silane-containing compounds of the general formula (II) are derived directly from the silane compounds of the general formula (I) as hydrolysis products and / or as condensation products. The hydrolysis and / or condensation of the compounds of the general formula (I) is particularly caused and influenced by the reaction conditions during the production of the adhesive, in particular acidic reaction conditions.
[0053] In the silane compound of formula (I), the residue X is advantageously selected from the group consisting of fluorine, chlorine, bromine, iodine, 1-6 Alkoxy, especially methoxy, ethoxy, n-propoxy and butoxy, C6-C 10 Aryloxy, especially phenoxy, C2-C7-acyloxy, especially acetoxy or propionyloxy, C2-C7-alkylcarbonyl, especially having C1-C 12 , especially C1-C6 acetyl, monoalkylamino or dialkylamino. Particularly preferred hydrolyzable groups are C1-C4 alkoxy, especially methoxy and ethoxy.
[0054] The silane compound preferably has a non-hydrolyzable organic residue R. In the context of the present invention, the term "non-hydrolyzable organic residue" is understood to mean an organic residue which, in the presence of water, does not lead to the formation of an OH group or NH2 group bonded to a Si atom. The non-hydrolyzable residue R is preferably selected from substituted and unsubstituted C1-C 30 Alkyl, especially C5-C 25 Alkyl, substituted and unsubstituted C2-C6 alkenyl, substituted and unsubstituted C2-C6 alkynyl, and substituted and unsubstituted C6-C 10 The non-hydrolyzable residue R is preferably selected from the group comprising methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, pentyl, hexyl, cyclohexyl, vinyl, 1-propenyl, 2-propenyl, butenyl, ethynyl, propargyl, phenyl and naphthyl.
[0055] The non-hydrolyzable residue R may have at least one functional group Q. In addition, the residue R may also be substituted by other residues. In one variant, the at least one functional group Q is selected from the group comprising epoxy, hydroxyl, ether, acrylic, acryloxy, methacryloyl, methacryloyloxy, amino, alkoxy, cyano and / or isocyano. In another variant, the at least one functional group Q contained in the organic non-hydrolyzable residue R advantageously comprises an epoxide, in particular a glycidyl or glycidyloxy, alkoxy, amino or isocyano group.
[0056] The polymer binder and the wood surface can be crosslinked via their crosslinking functional groups, in particular including polymerizable and / or polycondensable groups, wherein the polymerization reaction also includes a polyaddition reaction. Preferably, the functional groups are selected such that the organic crosslinking between the polymer binder and the wood surface and, if necessary, between different binder systems can be carried out by a polymerization and / or condensation reaction, if necessary catalyzed.
[0057] In a particularly preferred embodiment, tetraethoxysilane, methyltriethoxysilane, γ-isocyanatopropyltriethoxysilane or glycidoxypropyltriethoxysilane are used as silane.
[0058] The term "substituted" used with "alkyl", "alkenyl", "aryl", etc. means that one or more atoms (usually H atoms) are substituted with one or more of the following substituents, preferably with one or two of the following substituents: halogen, hydroxy, protected hydroxy, oxo, protected oxo, C3-C7 cycloalkyl, bicycloalkyl, phenyl, naphthyl, amino, protected amino, monosubstituted amino, protected monosubstituted amino, disubstituted amino, guanidinyl, protected guanidinyl, heterocycle, substituted heterocycle, imidazolyl, indolyl, pyrrolidinyl, C1 ... 12 Alkoxy, C1-C 12 Acyl, C1-C 12 Acyloxy, acryloyloxy, nitro, carboxyl, protected carboxyl, carbamoyl, cyano, methanesulfonylamino, thiol, C1-C 10 Alkylthio and C1-C 10 - Alkylsulfonyl. The substituted alkyl, aryl, alkenyl may be substituted one or more times, preferably one or two times, by the same or different substituents.
[0059] As used herein, the term "alkynyl" refers to a residue of the formula RC=C-, in particular "C-C6-alkynyl". Examples of C2-C6 alkynyl groups include: ethynyl, propynyl, 2-butynyl, 2-pentynyl, 3-pentynyl, 2-hexynyl, 3-hexynyl, 4-hexynyl, vinyl, and di- and tri-alkynyl groups of straight and branched alkyl chains. The term "aryl" as used herein refers to an aromatic hydrocarbon, such as phenyl, benzyl, naphthyl or anthracenyl. Substituted aryl is an aryl as defined above substituted by one or more substituents as defined above. The term "cycloalkyl" includes cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cycloheptyl.
[0060] In a preferred embodiment, the adhesive composition of the invention comprises at least two silane compounds, and particularly preferably two different compounds of the general formula (I) and / or (II). It is preferred that the first compound corresponds to the formula SiX4 (wherein X is OH or alkoxy, in particular methoxy, ethoxy, n-propoxy or isopropoxy) and the second compound corresponds to the formula R a SiX (4-a) (where a=1 or 2), wherein X is OH or alkoxy, especially methoxy, ethoxy, n-propoxy or isopropoxy, R is methyl, ethyl, N-propyl or N-butyl, and Q is glycidyl or glycidyloxy, alkoxy, amino or isocyano. Here, the molar ratio of the first compound to the second compound can be 0.1 to 1 mol, preferably 0.1 to 0.5 mol, particularly preferably 0.1 to 0.4 mol.
[0061] Furthermore, the amount of the reaction mixture of at least one silane compound, in particular a silane compound of the formula (I) and / or (II) and at least one polyol compound is preferably 1 to 20% by weight, particularly preferably 2 to 15% by weight, very particularly preferably 3 to 10% by weight, based on the amount of the polymer binder. The content of silane compound, hydrophilizing agent and / or phase transfer catalyst is preferably 1 to 30% by weight, particularly preferably 5 to 20% by weight, very particularly preferably 10 to 20% by weight. However, this information does not initially take into account the solvent content of the polymer binder used.
[0062] A particularly preferred variant of the adhesive composition of the invention comprises tetraethyl orthosilicate, glycidoxypropyltriethoxysilane, sorbitol, triethylbenzylammonium chloride as a phase transfer catalyst and PMDI glue as a polymer binder.
[0063] According to an advantageous improvement scheme of the method for producing wood materials of the present invention, the adhesive composition is added to the wood chip material in the form of two separate components of the adhesive composition, wherein one component is an organic phase containing a polymer adhesive, and the other component is at least one aqueous phase containing a phase transfer catalyst and / or a hydrophilizing agent. Alternatively, the phase transfer catalyst and / or the hydrophilizing agent are preferably added together with paraffin, wherein particularly preferably the phase transfer catalyst and / or the hydrophilizing agent are mixed with the paraffin in advance. Particularly preferably, the aqueous phase and / or the paraffin are applied to the wood chip material through a nozzle or atomizer in a mixer together with the phase transfer catalyst and / or the hydrophilizing agent or are sprayed on the wood chip material in a coil.
[0064] In a further preferred embodiment of the method according to the invention for producing wood material, the phase transfer catalyst and / or the hydrophilizing agent is added directly to the wood chip material to be combined and / or not first added to the organic phase containing the polymer binder, so that pre-reactions can be avoided particularly effectively, for example when the plant is on standby.
[0065] Although it is also feasible to produce a single-layer wood material, the wood material is preferably composed of at least two layers different from each other and / or composed of a lower covering layer, an intermediate layer and an upper covering layer, wherein at least one layer, preferably the intermediate layer, has an adhesive composition containing a phase transfer catalyst and a hydrophilic agent, and at least another layer has an adhesive composition that does not contain or contains a phase transfer catalyst and / or a hydrophilic agent at a lower concentration. The two covering layers preferably have the same adhesive composition and / or the same amount of adhesive as each other. Particularly preferably, the two covering layers are formed identically to each other. In addition, the concentration of the phase transfer catalyst and / or the hydrophilic agent in the top layer preferably corresponds to 25% to 75% of the concentration in the intermediate layer, preferably 40% to 60%, and particularly preferably 45% to 55%.
[0066] The content of the adhesive composition in the wood material board, in particular the OSB wood material board, is preferably 0.5 to 5.0 wt. %, particularly preferably 1.5 to 4.0 wt. %, very particularly preferably 2.0 to 3.0 wt. %, based on the total amount of wood fibers or wood chip material. In a preferred embodiment, the adhesive composition is sprayed onto the wood chips, the wood chip material or the wood fibers. DETAILED DESCRIPTION
[0067] The present invention is explained in more detail based on exemplary embodiments.
[0068] Embodiment 1:
[0069] At a facility producing OSB with three layers (one middle layer and two outer covering layers), the wood chip material called shavings of the middle layer of the coils was sprayed with a 12.5% Inosil GS 55 solution (as a silane compound) and a 20% TEBA (triethylbenzylammonium chloride) solution (as a phase transfer catalyst). The amount of Inosil GS 55 was 0.04% by weight based on dry wood and the amount of TEBA was 1.0% by weight based on dry wood.
[0070] Subsequently, the wood chips of the middle layer were sprayed with 2.0% by weight of PMDI (polymeric diphenylmethane diisocyanate) as a polymer binder and 1% by weight of paraffin wax. Then, 18 mm OSB was produced from the wood chips of the middle layer and the wood chips of the top layer, wherein 2.9% by weight of PMDI and 1.0% by weight of paraffin wax had been sprayed in the coil. The ratio between the top layer and the middle layer was the same in terms of quantity.
[0071] OSB equipment is 450mm / sec speed, conventional pressure (200-500N / cm 2 ) and conventional temperature (210-250°C) operation. The OSB produced according to the described parameters meets all the requirements of the standards applicable to this product.
[0072] However, when the same conditions were used without Inosil GS 55 and TEBA, the boards showed cracking, despite the use of the same amount of polymer adhesive and the same production speed, and the product quality was therefore judged as unacceptable. When OSB was produced with the above amounts of Inosil GS 55 or TEBA, OSB was obtained, but its transverse tensile strength was not high enough, less than 0.3 N / mm 2 The elastic module (E-Modul) of the board (longitudinal and transverse) is lower than the standard requirement.
[0073] Embodiment 2:
[0074] At a facility producing OSB with three layers (one middle layer and two outer covering layers), the wood chip material called wood chips of the middle layer of the coil was sprayed with a 12.5% Inosil GS 55 solution and a 20% TEBA (triethylbenzyl ammonium chloride) solution. The amount of Inosil GS 55 was 0.04% by weight based on dry wood and the amount of TEBA was 1.0% by weight based on dry wood. The wood chips were further sprayed with 2.0% by weight PMDI and 1% by weight paraffin.
[0075] The wood chips of the top layer were sprayed with 12.5% Inosil GS 55 solution and 20% TEBA (triethylbenzyl ammonium chloride) solution in a coil. The amount of Inosil GS 55 was 0.04% by weight based on dry wood and the amount of TEBA was 0.5% by weight based on dry wood. The wood chips were further sprayed with 2.5% by weight PMDI and 1% by weight paraffin.
[0076] 18 mm OSB is then made from the middle layer of wood and the top layer of wood. The ratio between the top layer and the middle layer is equal in quantity. The OSB facility is operated at a speed of 470 mm / sec and a conventional pressure (200-500 N / cm 2 ) and conventional temperature (210-250°C) operation. The OSB produced according to the described parameters meets all the requirements of the standards applicable to this product.
[0077] If the middle and outer layers were produced simultaneously without Inosil GS 55 and TEBA, the cracking phenomenon occurred again, although the same amount of polymer adhesive was used and the same production speed was maintained. When OSB was produced with the above-mentioned amounts of Inosil GS 55 or TEBA, the transverse tensile strength was again insufficient, below 0.3 N / mm 2 The elasticity module (E-Modul) of the board (longitudinal and transverse) was again below the standard requirements.
[0078] With the adhesive composition according to the invention, the plant can thus be used efficiently and the performance can be improved by up to about 30%. Furthermore, the amount of polymeric adhesive used can be kept low.
Claims
1. An adhesive composition for producing wood materials, the adhesive composition having - an organic phase containing at least one polymeric binder, - aqueous phase, - a phase transfer catalyst for accelerating the curing of the polymer binder, and A hydrophilic agent comprising at least one silane compound for increasing the hydrophilicity of the polymer binder and / or for reducing the penetration of the polymer binder into the material to be bonded of the wood material.
2. The adhesive composition for producing wood materials according to claim 1, characterized in that The phase transfer catalyst has onium ions and preferably has ammonium, phosphonium and / or sulfonium ions and is particularly preferably triethylbenzylammonium chloride.
3. The adhesive composition for producing wood materials according to claim 1 or 2, characterized in that The phase transfer catalyst is a crown ether, in particular 12-crown-4.
4. Adhesive composition for producing wood materials according to at least one of the preceding claims, characterized in that All polymer binders of the organic phase are polyurethane binders only.
5. Adhesive composition for producing wood materials according to at least one of the preceding claims, characterized in that The only polymer adhesive is a polyurethane adhesive based on polymeric diphenylmethane diisocyanate.
6. Adhesive composition for producing wood materials according to at least one of the preceding claims, characterized in that The hydrophilic agent comprises at least one polyol selected from the group consisting of tetravalent, pentavalent, hexavalent sugar alcohols or higher alcohols having more than six hydroxyl groups as a polyol compound.
7. The adhesive composition for producing wood materials according to claim 6, characterized in that The at least one sugar alcohol is selected from the group consisting of tetrahydric alcohols such as threitol, erythritol, and pentaerythritol, pentahydric alcohols such as arabitol, adonitol, and xylitol, and hexahydric alcohols such as sorbitol, mannitol, dulcitol, and dipentaerythritol.
8. Adhesive composition for producing wood materials according to at least one of the preceding claims, characterized in that The at least one silane compound is a compound of general formula (I) RaSiX (4-a) (I), Or general chemical formula (II) THE b X c (OH) d R e SiO(4-bcde) / 2(II), in -X is H, OH or a hydrolyzable residue selected from the group consisting of halogen, alkoxy, carboxyl, amino, mono- or di-alkylamino, aryloxy, acyloxy, alkylcarbonyl, -R is a non-hydrolyzable organic residue R selected from substituted and unsubstituted alkyl, substituted and unsubstituted aryl, substituted and unsubstituted alkenyl, substituted and unsubstituted alkynyl, substituted and unsubstituted cycloalkyl, which can be interrupted by -O- or -NH-, And among them - R can have at least one functional group Q selected from the group comprising epoxy, hydroxyl, ether, amino, monoalkylamino, dialkylamino, substituted and unsubstituted anilino, amide, carboxyl, alkynyl, acrylic, acryloxy, methacrylic, methacryloyloxy, mercapto, cyano, alkoxy, isocyanate, aldehyde, alkylcarbonyl, anhydride and / or phosphoric acid, - R and X can be the same or different from each other, and -a=0,1,2,3, especially 0 or 1, - b, c, d = 0 or 1, and -e=1、2、3。 9. A method for producing an adhesive composition according to any one of claims 1 to 8, the method comprising the following steps: - providing at least one silane compound, - adding at least one polyol compound, - preferably adding at least one catalyst, in particular an acid, to the mixture of at least one silane compound and at least one polyol compound, - precipitating and / or separating the reaction mixture from the at least one silane compound and the at least one polyol compound, - adding a phase transfer catalyst, and - adding at least one polymer binder system to the phase transfer catalyst and / or to the reaction mixture separated from the at least one silane compound and the at least one polyol compound.
10. A method for producing a wood material, the method comprising the following steps: - production and / or supply of wood chip materials, - adding a binder composition to the wood chip material, wherein the binder composition comprises an organic phase containing at least one polymer binder and a second aqueous phase immiscible with the organic phase, a phase transfer catalyst for accelerating the curing of the polymer binder and a hydrophilizing agent comprising at least one silane compound to increase the hydrophilicity of the polymer binder and / or reduce the penetration of the polymer binder into the wood material to be bonded to the wood chip material, - forming a wood material from the bonded wood chip material, in particular by pressing into a board-shaped wood material.
11. The method for producing wood material according to claim 10, characterized in that The binder composition is added to the wood chip material in the form of two separate components of the binder composition, one of which is an organic phase containing a polymer binder and the other is at least one aqueous phase containing a phase transfer catalyst and / or a hydrophilizing agent.
12. The method for producing wood material according to claim 10 or 11, characterized in that The phase transfer catalyst and / or the hydrophilizing agent are added directly to the wood chip material to be bound and / or without first being added to the organic phase containing the polymeric binder.
13. Method for producing wood material according to at least one of the preceding claims 10 to 13, characterised in that The wood material consists of at least two layers different from each other and / or consists of a lower covering layer, a middle layer and an upper covering layer, wherein at least one layer, preferably the middle layer, has an adhesive composition containing a phase transfer catalyst and a hydrophilic agent, and at least another layer has an adhesive composition that does not contain or contains a lower concentration of a phase transfer catalyst and / or a hydrophilic agent.
14. The method for producing wood material according to claim 13, characterized in that The two covering layers have the same adhesive composition and / or the same amount of adhesive and / or the concentration of the phase transfer catalyst and / or the hydrophilic agent in the covering layers corresponds to between 25% and 75% of the concentration in the intermediate layer, preferably between 40% and 60%, particularly preferably between 45% and 55%.
15. A wooden material, in particular a wooden material produced by a method according to at least one of claims 10 to 14, comprising at least one wood chip material and at least one cured adhesive composition in at least one layer of the wooden material, in particular an adhesive composition according to at least one of claims 1 to 8, wherein the adhesive composition has at least one cured polymer adhesive, a phase transfer catalyst for accelerating the curing of the polymer adhesive and a hydrophilic agent comprising at least one silane compound to increase the hydrophilicity of the polymer adhesive and / or reduce the penetration of the polymer adhesive into the wood chip material to be bonded to the wooden material.